2021
DOI: 10.1111/acfi.12887
|View full text |Cite
|
Sign up to set email alerts
|

ASX small firm/microcap listings: the IPO ‘Pop’ and two decades of subsequent returns

Abstract: We examined IPO discounts and average returns for all available ASX (de)/listed IPOs from 1999 to 2019. We found that the average 18.45 percent offering discount was close to that observed in the US, as were the discount time series behaviour and distribution. Furthermore, the average annualised return on a market‐weighted portfolio of the ASX small/microcap IPOs, from close‐of‐listing‐day price to delisting or 31 December 2019, is 18.62 percent compared to 2.28 percent for large‐caps. Small/microcap post‐list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The ASX's success in listings since the turn of the millennium greatly differs from other developed markets. Since the 1980s, the ASX has steadily increased its number of listed companies (from 982 in 1980), with 78% of new listings being early-stage small or microcapthose with AU$75m or less in total market capitalisation at IPO (Gilbey et al, 2022). The ASX IPO experience contrasts with that of the USA, where the number of listed firms has steadily declined from a peak of over 8,000 companies in 1997 to just 4,266 companies in 2019 [4].…”
Section: The Asxmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASX's success in listings since the turn of the millennium greatly differs from other developed markets. Since the 1980s, the ASX has steadily increased its number of listed companies (from 982 in 1980), with 78% of new listings being early-stage small or microcapthose with AU$75m or less in total market capitalisation at IPO (Gilbey et al, 2022). The ASX IPO experience contrasts with that of the USA, where the number of listed firms has steadily declined from a peak of over 8,000 companies in 1997 to just 4,266 companies in 2019 [4].…”
Section: The Asxmentioning
confidence: 99%
“…In recent decades, the Australian Securities Exchange (ASX) has managed to defy the significant global decline in smaller company exchange listings (Jensen et al, 2021). This was accomplished primarily by allowing the listing of small early-stage companies on the main exchange board under the same regulatory listing requirements as their larger counterparts (Gilbey et al, 2022). Over the past two decades, in allowing listings ranging from AU$3m to $6bn in market capitalisation, 78% of which are predominantly small/micro "emerging" company listings, the ASX has effectively extended the supply of public new-listing…”
Section: Introductionmentioning
confidence: 99%
“…Industry discussions indicate that WA is felt to hold a higher risk appetite within the regional ecosystem for earlier stage, smaller companies that seek to be listed on the ASX. Therefore, to explore this proposition, we examined the IPO data sample of Gilbey et al (2021), who identified 2,018 IPOs conducted on the ASX from January 1999 to December 2019. Guided by Rose and Solomon (2016), Gilbey et al (2021) divided the IPO sample into three sizes using the market capitalisation of firms at IPO dates: (i) small-cap IPOs: < $75 million market capitalisation upon listing; (ii) middle-cap IPOs: $75-$700 million market capitalisation upon listing; and (iii) large-cap IPOs: > $700 million market capitalisation upon listing (Rose & Solomon, 2016).…”
Section: Asx Ipo Characteristicsmentioning
confidence: 99%
“…Therefore, to explore this proposition, we examined the IPO data sample of Gilbey et al (2021), who identified 2,018 IPOs conducted on the ASX from January 1999 to December 2019. Guided by Rose and Solomon (2016), Gilbey et al (2021) divided the IPO sample into three sizes using the market capitalisation of firms at IPO dates: (i) small‐cap IPOs: < $75 million market capitalisation upon listing; (ii) middle‐cap IPOs: $75–$700 million market capitalisation upon listing; and (iii) large‐cap IPOs: > $700 million market capitalisation upon listing (Rose & Solomon, 2016). The results for IPO capital raised between 1 January 1999 to 31 December 2019 are summarised in Table 3.…”
Section: Empirical Review: Australian Securities Exchange Industry An...mentioning
confidence: 99%
See 1 more Smart Citation